2014
DOI: 10.1111/jcc4.12083
|View full text |Cite
|
Sign up to set email alerts
|

Fear Appeals, Message Processing Cues, and Credibility in the Websites of Violent, Ideological, and Nonideological Groups

Abstract: Ideological groups use the Internet to deliver their messages unhindered by the constraints of traditional media. We examined how ideological groups promote their worldview through their websites. Using the elaboration likelihood model (ELM), this research used trained coders to examine the websites of nonideological groups (n = 37), nonviolent ideological groups (n = 36), and violent ideological groups (n = 32) for credibility, persuasion processing cues, and interactivity factors. Results of this study found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 55 publications
(79 reference statements)
0
7
0
Order By: Relevance
“…Websites were designed to be similar in structure and content to other ideological websites on the internet, as assessed through past work (Connelly et al, 2015;Dunbar et al, 2014;Jensen et al, 2014). For example, both websites included features such as an about page, FAQ and events page.…”
Section: Website Designmentioning
confidence: 99%
“…Websites were designed to be similar in structure and content to other ideological websites on the internet, as assessed through past work (Connelly et al, 2015;Dunbar et al, 2014;Jensen et al, 2014). For example, both websites included features such as an about page, FAQ and events page.…”
Section: Website Designmentioning
confidence: 99%
“…Credibility is comprised of judgments of a sources' expertise and trustworthiness; expertise is a set of "skills, competencies, and characteristics that enable a party to have influence within some specific domain" (Mayer et al, 1995, p. 717), while trustworthiness is defined as the ability, benevolence, and integrity of a source that provides health information (Mayer et al, 1995). ELM-based studies have shown that receivers often make judgments of credibility on the basis of the source's physical appearance or social status (Dunbar, et al, 2014;Emmers-Sommers & Teran, 2020), so it is not surprising that physical appearance cues like professional clothing, scrubs, or lab coats are often cited as cues that Perceived expertise and trustworthiness 7 enhance the credibility of recruiters (Harrigan, et al, 2014;Morgan et al, 2018;. Perceived similarity of personal traits, particularly race (i.e., homophily) also plays an important role in establishing trustworthiness (Berry et al, 2018).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Thus, the success of an ideological website is not measured monetarily, but rather, in the influence it exerts on viewers' beliefs, values, and actions Dunbar et al, 2014). Because there is a need to better understand perceptions of online credibility in ideological groups and the role of pre-existing attitudes in those perceptions, we conducted two studies to test aspects of Metzger and colleagues' (2010) theory of social and heuristic approaches to online credibility evaluation in an online ideological setting.…”
Section: Introductionmentioning
confidence: 99%